Centering Equity and Justice in the Emerging Concept of Nature-Based Solutions in Massachusetts - Sheinbaum, Perri. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisors: Julian Agyeman, and Christine Cousineau.; Keywords: Urban planning, and Environmental management.